Cigarette smoke aggravates asthma via altering airways inflammation phenotypes and remodelling - Qiong Huang; Yan Li; Chenduo Li; Xin Zhang; Xiaonan Du; Yan Chen; Chris J. Corrigan; Wei Wang; Sun Ying (The Clinical Respiratory Journal, 2023)
Abstract Introduction Many asthmatic patients are exposed to cigarette smoke actively or passively, which contributes to asthma exacerbation and poor control. This study is to explore the effects of cigarette smoke on pathological changes in murine surrogate of asthma. Methods C57BL/6 mice were sensitised and challenged with ovalbumin (OVA) to establish a surrogate of asthma and then administered with cigarette smoke extract (CSE). Airways hyperresponsiveness (AHR) was measured using the Flexivent system. Histological staining (haematoxylin‐eosin [HE], periodic acid Schiff [PAS], Congo red and Masson's trichrome) was employed to measure pathological changes in sections of lung tissue of experimental mice. Enzyme‐linked immunosorbent assay (ELISA) was used to measure the concentrations of total and OVA‐specific IgE, cytokines and chemokines (eotaxin‐1, IL‐13, IL‐1β, TNF‐α, IL‐17A, IL‐33) in the lung tissue homogenates. Immunoreactivity for vWF and α‐SMA in lung tissue sections was detected by immunohistochemistry. Results Exposure of the animals to CSE significantly reduced OVA‐induced AHR, the number of eosinophils in bronchoalveolar lavage fluid (BALF) and eosinophils infiltrating into the lung tissue, as well as concentrations of some cytokines in lung homogenate. In contrast, it significantly enhanced the number of macrophages and M2 in BALF, as well as collagen deposition, smooth muscle thickness and alveolar destruction in lung tissue. Conclusion CSE inhibits OVA‐induced AHR, changes inflammation ‘phenotypes’, while accelerates some aspects of airways remodelling, which might contribute to worse symptoms and be refractory to anti‐inflammation therapies for asthmatics.